Atrial fibrillation in emergency department: prevalence of sinus rhythm 1 week after discharge. Issue 4 (25th March 2011) - Fundarò, Camilla; Galli, Andrea; Paglia, Stefano; Colombo, Silvia; Rovellini, Angelo; Colombo, Livio; Monzani, Valter; Coen, Daniele; Guzzetti, Stefano
Abstract : Background: Current guidelines do not provide definitive indications about the treatment in emergency departments (ED) of patients with recent-onset atrial fibrillation (AF). Methods: A multicentre observational study involving four general hospitals of the same metropolitan area was conducted. All consecutive adult patients admitted to the ED with recent symptoms of AF (<48 h duration) and discharged home were considered. Patients who underwent ED early cardioversion were enrolled in group A. Patients managed with ventricular rate control were enrolled in group B. Results: On the 24 h Holter recordings at 1-week follow-up, stable sinus rhythm was detected in 46/58 (79.3%; 95% CI 68.9 to 89.7) patients in group A and 8/33 (24.2%; 95% CI 9.6 to 38.9) patients in group B (p<0.01). Conclusion: According to the study results, rhythm at the time of ED discharge is a poor indicator of the short-term evolution of AF.